Opinie właścicieli gospodarstw rolniczych dotyczące sporządzania budżetów przepływów pieniężnych - Wasilewski, Mirosław; Forfa, Magdalena (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The paper presents individual farmers’ opinions concerning on creating cash flow budget. Research objectives were individual farms from podlaskie voivodships participating in the FADN (46 farmers). The results of the interview questionnaire indicate that farmers draw up cash flow budget in order to efficient the financial management of farms. Most of the farmers said that they examine the balance of cash flows from operating, investing, financial and private activities.